Implementation Of Good Environmental Governance in Waste Management to Realize Indonesia's Zero Waste 2040 Vision - Uswatun Asiah (Future Science, 2025)
This study aims to analyze the application of the principles of Good Environmental Governance in waste management to realize Indonesia Zero Waste 2040. Currently, the presence of waste in Indonesia signals a state of emergency; improper waste management causes waste to continue accumulating and creates problems in various aspects. So far, waste management has used a collect-transport-dispose paradigm, so this method has not yet been able to resolve the waste problem. This study employs a descriptive qualitative method, aiming to describe, analyze, and assess the application of Good Environmental Governance (GEG) in waste management in Indonesia and its relevance to the Zero Waste 2040 agenda. The researcher also uses a national policy approach and environmental governance theory because issues of waste management and the Zero Waste 2040 target are part of the national sustainable development agenda. Research results show that to achieve Indonesia Zero Waste 2040, there are several principles that must be implemented, such as the rule of law, public participation, access to information, transparency, accountability, and the existence of effective institutions for enforcement and resolution of environmental disputes. From this research, it can be concluded that the implementation of GEG principles is still not optimal, for example, the enforcement of the rule of law has not provided strict sanctions against individuals who dispose of waste carelessly, whether at the household level, small-medium industries, or large industries.